Some remarks on bv(s)-metric spaces and fixed point results with an application - Garai, Hiranmoy; Dey, Lakshmi Kanta; Mondal, Pratikshan; Radenović, Stojan (Nonlinear Analysis: Modelling and Control, 2020)
We compare the newly defined bv(s)-metric spaces with several other abstract spaces like metric spaces, b-metric spaces and show that some well-known results, which hold in the latter class of spaces, may not hold in bv(s)-metric spaces. Besides, we introduce the notions of sequential compactness and bounded compactness in the framework of bv(s)-metric spaces. Using these notions, we prove some fixed point results involving Nemytzki–Edelstein type mappings in this setting, from which several comparable fixed point results can be deduced. In addition to these, we find some existence and uniqueness criteria for the solution to a certain type of mixed Fredholm–Volterra integral equations.
Keywords: boundedly compact space; sequentially compact space; contractive mapping; bv(s)-metric spaces